2006
DOI: 10.1539/joh.48.332
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Job Strain with Coronary Heart Disease and Metabolic Syndrome in Municipal Workers in Turkey

Abstract: The Association of Job Strain withCoronary Heart Disease and Metabolic Syndrome in Municipal Workers in Turkey: Yucel DEMIRAL, et al. Department of Public Health, Dokuz Eylül University School of Medicine, Turkey-To explore the association of job strain with CHD and metabolic syndrome in municipal workers. A cross-sectional study was completed of 450 male workers. Coronary heart disease was defined as: physician diagnosed ischemic heart disease; and/or, ischemic findings in the ECG. Metabolic syndrome was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 22 publications
2
26
0
7
Order By: Relevance
“…Optamos por trabalhar com os quadrantes por ser a alternativa que mais reflete a concepção dos autores da escala, além de ser uma forma de análise bastante utilizada, o que favorece comparações futuras. Quanto ao melhor ponto de corte dos escores de demanda e controle para constituição dos quadrantes, optamos pelo uso da mediana, a medida mais comumente utilizada 26,27,28 .…”
Section: Discussionunclassified
“…Optamos por trabalhar com os quadrantes por ser a alternativa que mais reflete a concepção dos autores da escala, além de ser uma forma de análise bastante utilizada, o que favorece comparações futuras. Quanto ao melhor ponto de corte dos escores de demanda e controle para constituição dos quadrantes, optamos pelo uso da mediana, a medida mais comumente utilizada 26,27,28 .…”
Section: Discussionunclassified
“…The Turkish version of the Swedish job demand-control-support scale is used to measure work stress 20) . The scale contains 17 items.…”
Section: Methodsmentioning
confidence: 99%
“…However, women with low long-term job strain were reported to have high levels of metabolic syndrome, whereas men with high long-term job strain showed low levels of metabolic syndrome (Kinnunen, Feldt, Kinnunen, Kaprio, & Pulkkinen, 2006). And at least one recent study found no relationship between job strain and metabolic syndrome (Demiral, et al, 2006). This area must therefore be considered to require further exploration.…”
Section: Metabolic Syndromementioning
confidence: 99%